2015
DOI: 10.9734/bmrj/2015/16339
|View full text |Cite
|
Sign up to set email alerts
|

Keratin Degradation by Penicillium purpurogenum Isolated from Tannery Soils in Jos, Nigeria

Abstract: Background: Tannery soils are very rich in keratinous materials such as fur, wool and hair that are by-products of the tanning industry where hides and skins are processed. A keratinase producing fungus belonging to the genus Penicillium was isolated from soils containing tannery wastes in Jos, Plateau State Nigeria. Materials and Methods: The fungus produced extra cellular protease on skim milk casein agar as an indication for keratinase production. The species had maximum proteolytic and keratinase activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The high frequencies of some fungi could be explained by the fact that these species are polyphagous and ubiquitous likely to live on more diverse substrates. The number of species of the isolated fungi (6 species) is less than those obtained by Dongmo et al (2017), (12 fungal species) on Ricinodendron heudelotii and Garcinia kola almonds in Western Cameroon and by Nwadiaro et al (2015) on P. biglobosa seeds in Nigeria (17 fungal species). This difference can be explained on the one hand by the higher temperatures in Chad which are not favourable to the development of hygrophilic fungi and on the other hand by the nature of the seeds studied.…”
Section: Post-harvest Fungi Identifiedmentioning
confidence: 79%
See 1 more Smart Citation
“…The high frequencies of some fungi could be explained by the fact that these species are polyphagous and ubiquitous likely to live on more diverse substrates. The number of species of the isolated fungi (6 species) is less than those obtained by Dongmo et al (2017), (12 fungal species) on Ricinodendron heudelotii and Garcinia kola almonds in Western Cameroon and by Nwadiaro et al (2015) on P. biglobosa seeds in Nigeria (17 fungal species). This difference can be explained on the one hand by the higher temperatures in Chad which are not favourable to the development of hygrophilic fungi and on the other hand by the nature of the seeds studied.…”
Section: Post-harvest Fungi Identifiedmentioning
confidence: 79%
“…Therefore, the application of EO, and African Panax as a treatment product are essential for this purpose. The study conducted by Nwadiaro et al (2015) on locust bean seeds in Nigeria showed that colonization of the seeds by post-harvest fungi significantly reduced the nutrient content of the seeds.…”
Section: Germination Infection and Seedlings Vigour Indexmentioning
confidence: 99%
“…Keratin renders animals more robust against both abiotic stress and, which is its most important function, microbial attack . Although only a few species of prokaryotic organisms, that is, Bacillus licheniformis or Bacillus subtilis, are equipped with enzymes with keratin degradation activity, these enzymes commonly occur in dermatophytes, that is, Trichophyton verrucosum, Trichophyton mentagrophytes, Trichophyton equinum, Trichophyton gallinae, Microsporum canis and many more, but rarely in other eukaryotic microorganisms, that is, Aspergillus niger, Aspergillus flavus, Penicillium purpurogenum or Fusarium solani . Thus, microbial degradation of keratin is not widespread in nature outside the dermatophyte group, and keratin can serve as an efficient defence even against microbial attack …”
Section: Discussionmentioning
confidence: 99%